Hoezo wetenschappelijke vorming? Over rendementen en de functies van de Universiteit van Amsterdam, 1877-1940 - Knegtmans, Peter Jan (Studium, 2019)
For more than a century, professors in the Netherlands have claimed that the Dutch universities educated students for scholarly practice. And indeed, this is what in the 1876 Act on Higher Education was formulated as one of the purposes of the universities: educating and preparing students for independent scholarly practice and to prepare them for holding posts in society for which a scholarly training was required. For this article I have investigated how many of the more than 16.000 students of the University of Amsterdam who enrolled between 1877 and 1937 actually graduated. The result shows that until the Second World War, only a very small part of these students did scholarly research during their studies. For the majority of students, the university mainly acted as a set of professional schools in preparing students for holding posts for which a scholarly training was required.